Development of fish therapy pond edutourism in Magelang Pine Valley - Ilham Majida Yasa; Yunita Yunita; Barkah Susanto; Betari Maharani; Nur Hidayah; Ericka Darmawan; Ani Setiyowati; Syuhada Abdi Ra’uuf; Asifa Nas Arif; Rizqil Ghozi Mubarok (Universitas Muhammadiyah Magelang, 2024)
Lembah Pinus Magelang, located in Surodadi Village, Tepus Wetan Hamlet, faces challenges due to a lack of diverse tourist attractions, leading to low tourist interest and limited competitiveness of the area. To address this issue, the community service initiated the development of a fish therapy pond as a new attraction. This program was carried out in three main stages: identifying existing and supporting facilities, socializing the potential for fish therapy pond development with Pokdarwis Mekar Lestari, and assisting in the construction process of the fish therapy pond. The initial identification revealed that existing facilities, such as children’s play areas, outbound spaces, and camping grounds, were insufficient to sustainably attract visitors. The fish therapy pond was developed with an environmentally friendly design and involved the local community in its management. This new attraction successfully increased the area’s appeal, as evidenced by a rise in visitor numbers from 500 to 1,200 within two months after its opening. An entry fee of IDR 2,000 per visitor also contributed to additional income for the community through sustainable management. This program not only enhanced the diversity of tourist attractions at Lembah Pinus Magelang but also empowered the local community in managing tourism resources. The long-term impact is expected to include improved local economic development, better tourism management, and strengthened competitiveness of the area as a leading natural tourism destination.